Penerapan Metode Diskusi Kelompok Model Pembelajaran Jigsaw untuk Meningkatkan Hasil Belajar IPA dalam Materi Gerak Benda Siswa Kelas III Sekolah Dasar - Sumarti Sumarti (Universitas Sebelas Maret, 2021)
The purpose of this research is increasing the Third Grade students’ of 2Pasarbanggi General Elementary School on Natural Science learning results about the ObjectMovement through the application of group discussion method with Jigsaw learning model.This research is a Class Action Research (CAR) that consists of 2 cycles and going on 2ndSemester 2018/2019 Year Academic. The subjects of this research are 18 students. Thetechniques of collecting data are test and non test. The technique of analyzing data isdescriptive. The result of this research is the increasing of the learning results. The learningresults on the Pre cycle are 60,9 for the average and 39% for the completeness. The learningresults on the First Cycle are 73,1 for the average and 72% for the completeness. The learningresults on the Second Cycle are 75,7 for the average and 94% for the completeness.